Awareness regarding human papillomavirus and willingness for vaccination among college students with or without medical background in Guizhou Province - Qiongdan Hu; Yuanqin Rui; Jing Jiang; Jing Yang; HanYun Yao; XiaoFang Yang; Zhe Liu; Chencui Li; Hong Pan; Yan Xie (Taylor & Francis Group, 2024)
ABSTRACTThis cross-sectional epidemiological study aimed to investigate awareness regarding human papillomavirus (HPV) and willingness for vaccination among college students with or without medical background in Guizhou Province, China. A logistic regression model was used for univariate and multivariate analyses of cognition to determine factors influencing willingness for vaccination. In total, 2,540 questionnaires were collected, of which 2,360 were valid. The medical and nonmedical groups included 737 (31.2%) and 1,623 (68.8%) individuals, respectively. The medical group had heard of HPV and its vaccines more frequently than the nonmedical group, with the former also having greater awareness than the latter (P < .001). Females (1,325, 56.1%) had heard of HPV and its vaccines more frequently than males (1,035, 43.9%), with the former also having greater awareness than the latter. The cost, safety, and efficacy of the HPV vaccine and lack of knowledge regarding HPV and its vaccines were the main barriers for vaccination. The overall level of knowledge regarding HPV and its vaccines was lower in the nonmedical group and males than in the medical group and females. To help promote willingness for vaccination among the nonmedical group and males, strategies that deepen their knowledge regarding the HPV vaccine are needed.